End-Effector Path Planning and Collision Avoidance for Robot-Assisted Surgery - Quoc Cuong Nguyen; Kim, Youngjun; Park, Sehyung; Kwon, HyukDong (KOREAN SOC PRECISION ENG, 2016)
The limited workspace and potential for collision between the robot arm and surrounding environment are challenges in robot assisted surgery. In robot-assisted surgical procedures, the surgical robot's end-effector must reach the patient's anatomical targets without collision with the patient or surrounding instrument. This paper proposes a novel end-effector path planning method for a robot-assisted surgical system. A collision detection and avoidance method was also developed to create a collision-free path to enhance patient safety. The proposed algorithm also addresses how to update the planned path when the patient moves during a surgical procedure. Experimental results showed that the proposed method successfully solves the path planning and collision avoidance problem in robot-guided surgery.
Keywords: ANTERIOR CRUCIATE LIGAMENT; DOUBLE-BUNDLE; RECONSTRUCTION; SYSTEM; NAVIGATION; PLACEMENT; TUNNEL